Commodification and Cultural Resilience in Biologically High-Risk Culinary Tourism: A Case of Lawar Plek in Bali - I Gusti Ayu Eka Suwintari; I Made Trisna Semara; Putu Indah Budi Apsari; I Putu David Adi Saputra (Politeknik Pariwisata Makassar, Indonesia, 2026)
This study aims to analyze the resilience strategies of Lawar Plek, a traditional Balinese dish utilizing raw blood, and to explain how its risk-culture paradox is managed within the culinary tourism industry amidst conflicting medical health narratives and the market demand for cultural authenticity. Employing a qualitative case study design, research was conducted in major culinary centers across Gianyar and Badung Regencies. Data were gathered through participant observation, document analysis, and in-depth interviews with purposively selected key informants representing traditional vendors, local consumers, and external stakeholders. Rather than conducting laboratory biomedical testing, this study evaluates the negotiation between community perceptions of cultural authenticity and global biomedical health standards, analyzing how the latter is internalized or resisted by cultural actors. The analysis, guided by commodification and cultural resilience theories, reveals that the resilience of Lawar Plek is driven by a